Beginning pre-school at 4 years old : an analysis of parents' and educators' views - Noorizan bt. Baba (Institute of Education, International Islamic University Malaysia, 2009)
This study attempted to find out the factors that influence parents to enroll their children in Preschool at the age of 4 years old. The study involved parents of 4 years old children from 13 preschools or kindergartens in Ulu Kelang district and selected educators in Kuala Lumpur. Ninety three participants were selected through purposive sampling procedure. This study employed the survey design. Data was collected using a self-constructed survey instrument and structured-interview questions which were reported verbatim. The findings of this study revealed that the factors influencing parents to enroll their 4 year old child to preschool were the parents' expectation and commitment to give the best education to their children; the parents also expected the preschool to provide the best facilities and qualified staff for their children; most of the parents believed that their child should learn the basic skills of 3Rs and they were confident that their children can face all the difficulties in the learning process. The interview session with the parent participants added more factors which indicated that the parents were aware on the importance of socialization to their child, they wanted their children to acquire the primary school basic skills and only a few of the parents sent their child to preschool for day care reason. With regard to the parents' expectation in the worthiness of sending their 4 years old children to preschool, this study found that most of the parents expected their children to develop the social skills. Some parents hoped it will be a preparation toward school; they wanted their children to have fun learning experience in the preschool and at the same time to prepare the children with academic readiness.